Applying magnetic-responsive nanocatalyst-liquid interface for active molecule manipulation to boost catalysis beyond diffusion limit - Nur Amalina Mohamed-Ibrahim (2022)
Efficient nanocatalysis requires swift delivery of reactants to catalytic sites, but the presence of diffusion-dominated, hydrodynamic boundary layers on all heterogeneous catalysts impedes fast chemical transformation. Here, efficient nanocatalysis is achieved by applying a magnetic-responsive nanocatalyst-liquid interface to create a vortex-like flow that rapidly pulls reactants from bulk solution to the catalyst, beyond the diffusion limit. Consequently, our design attains a >90 % degradation efficiency in <5 min with reaction kinetics tunable via the nanocatalyst spin rate. The spinning nanocatalyst notably exhibits reaction kinetics and molecule transfer rates >10-fold and 30-fold faster than traditional homogenization methods, respectively. This unique molecule delivery design will complement recent advances in active catalytic nanomaterials to realize ideal nanocatalysis in emerging chemical, energy, and environmental applications.